Does IFRS Help Us Communicate Better? Redifinisi Kualitas Informasi Akuntanis Dalam Perspektif Strategik Pelaporan Keuangan - Utpala Rani; Supanji Setyawan (Accounthink, 2018)
Financial reporting should not only provide benefits to external stakeholders, but it should also provide benefits to the company's susrvival efforts. Therefore, this study elaborates a strategic perspective to define the quality of accounting information. By adopting the concept of qualitative characteristics of IASB and resource-based financial statements, this study provides a theoretical framework for the development of advanced studies on the strategic role of accounting reporting